POLARIZED NEUTRON REFLECTION USED TO CHARACTERIZE COBALT COPPER MULTILAYERS - Schwarzacher, W; Allison, W; Penfold, J; Shackleton, C; England, C; Bennett, W; Dutcher, J; Falco, C (1991)
The polarized neutron reflectivity (PNR) of cobalt/copper multilayer films has been measured close to the critical edge for total reflection. Prominent features in the scattered neutron intensity, such as the superlattice diffraction peaks and the positions of the critical edge for total reflection, are sensitive to both the magnetic and structural properties of films, making PNR a useful tool for the characterization of magnetic metallic superlattices. The films were prepared by sputter deposition and the sample composition was measured by Rutherford backscattering spectroscopy. It has been found that while the density of the sputtered copper/cobalt multilayers is approximately 5% less than the bulk metals, the cobalt magnetic dipole moment per atom is little changed compared to the bulk. Evidence is also found for oxidation of the top cobalt layers.